2016
DOI: 10.1002/anie.201605397
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Lewis Acid Sites for the Selective Catalytic Reduction of Nitric Oxide on Vanadium‐Based Catalysts

Abstract: The long debated reaction mechanisms of the selective catalytic reduction (SCR) of nitric oxide with ammonia (NH3 ) on vanadium-based catalysts rely on the involvement of Brønsted or Lewis acid sites. This issue has been clearly elucidated using a combination of transient perturbations of the catalyst environment with operando time-resolved spectroscopy to obtain unique molecular level insights. Nitric oxide reacts predominantly with NH3 coordinated to Lewis sites on vanadia on tungsta-titania (V2 O5 -WO3 -TiO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
225
3
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(253 citation statements)
references
References 34 publications
18
225
3
1
Order By: Relevance
“…But there is no clear consensus because several investigations suggested that Lewis acid centers could be also involved. Indeed, Marberger et al . through time‐resolved spectroscopic measurements pointed out the involvement of Lewis acid sites on vanadate species which seems consistent with higher Turn‐Over‐Frequency values compared to those estimated on Brønsted acid sites …”
Section: The Surface Chemistry Of Benchmark V2o5 Scr‐catalysts: Whatsupporting
confidence: 61%
See 1 more Smart Citation
“…But there is no clear consensus because several investigations suggested that Lewis acid centers could be also involved. Indeed, Marberger et al . through time‐resolved spectroscopic measurements pointed out the involvement of Lewis acid sites on vanadate species which seems consistent with higher Turn‐Over‐Frequency values compared to those estimated on Brønsted acid sites …”
Section: The Surface Chemistry Of Benchmark V2o5 Scr‐catalysts: Whatsupporting
confidence: 61%
“…Despite, adsorbed NH 4 + species (ads‐NH 4 + ) dominates, adsorbed NH 3 intermediates on Lewis sites were found exhibiting higher TOF values. Marberger et al . also found from time resolved‐Diffuse Reflectance Infrared spectroscopy (DRIFT) and Diffuse Reflectance Visible spectroscopy (DR‐Vis) that NO reacts preferentially with adsorbed ammonia species bonded to Lewis sites on V 2 O 5 −WO 3 /TiO 2 instead of Brønsted acid sites.…”
Section: The Surface Chemistry Of Benchmark V2o5 Scr‐catalysts: Whatmentioning
confidence: 99%
“…Arnarson et al [4] observed the SCR reaction over the VO 3 H/TiO 2 catalyst and demonstrated that the Brønsted acid site served to capture the NH 3 and increased the NH 4 + stability (increased Brønsted acid strength), which impacted the catalytic rate in a negative direction. Marberger et al [5] had a similar conclusion for the V 2 O 5 -WO 3 /TiO 2 catalyst. That is, the Brønsted acid sites hardly contributed to the SCR activity and mainly served as an NH 3 pool to replenish the Lewis sites.…”
Section: Introductionmentioning
confidence: 56%
“…Vanadium‐based materials play an important role in heterogeneous catalysis. Redox properties present in vanadium oxides are very useful to promote significant chemical processes, like oxidations, ammoxidations and reductions . An important parameter that induces catalytic properties in vanadium‐based materials is the support's surface coverage.…”
Section: Introductionmentioning
confidence: 99%